Evaluation of vitamin E addition in the diet for decreasing malondialdehide value and lead accumulation in the nile tilapia Oreochromis niloticus (Linnaeus, 1758)] - Sheny Permatasari; Nur Bambang Priyo Utomo; Kukuh Nirmala (Jurnal Iktiologi Indonesia, 2016)
This study aimed to evaluate the effect of the different doses of vitamin E in diet toward malondialdehide value and accumulation of heavy metal of Tilapia Oreochromis niloticus (Linnaeus 1758) exposed by lead (Pb). This study consists of four treatments, three replications and one negative control which was analyzed with descriptive method. Vitamin E supplementation treatments in the diet were KN (negative control 0 mg kg-1 , no exposed by lead); KP (positive control 0 mg kg-1 ); P100 (100 mg kg-1 ); P300 (300 mg kg-1 ); P500 (500 mg kg-1 ). Tilapia (13.17±1.06 g fish-1 ) were reared in 15 aquariums (135 liters volume) with a density of 13 fish in each aquarium for 60 days exposed by lead with 9.119 mg L-1 concentrations (except negative control). Fish were fed thrice a day at at 08.00 am, 12.00 pm, and 16.00 pm with the satiation level. An addition of Vitamin E alpha-tocopherol of 100 mg kg-1 in diet exposed by lead could decrease the accumulation of lead and MDA in fish liver of 1.47 mg kg-1 and 5.41 µg g-1, respectively. Abstrak Penelitian ini bertujuan untuk mengevaluasi pengaruh penambahan vitamin E dengan dosis berbeda pada pakan terha- dap nilai malondialdehid hati dan akumulasi logam berat pada tubuh ikan nila Oreochromis niloticus (Linnaeus, 1758) yang terpapar timbal (Pb). Rancangan penelitian yang digunakan adalah rancangan acak lengkap dengan empat perlaku- an dan tiga ulangan, dan satu perlakuan kontrol negatif yang diolah secara deskriptif. Perlakuan penambahan vitamin E: KN (kontrol negatif 0 mg kg-1 tanpa paparan Pb); KP (kontrol positif 0 mg kg-1 ); P100 (100 mg kg-1 ); P300 (300 mg kg-1 ); P500 (500 mg kg-1 ). Ikan nila (13,17±1,06 g ekor -1 ) dipelihara dalam 15 akuarium (volume 135 liter) dengan ke- padatan 13 ekor akuarium-1 selama 60 hari paparan Pb konsentrasi 9,119 mg L-1 kecuali kontrol negatif tanpa paparan. Ikan diberi pakan secara at satiation sebanyak tiga kali sehari pada pukul 08.00, 12.00, dan 16.00. Hasil penelitian me- nunjukkan bahwa vitamin E alpha-tokoperol sebanyak 100 mg kg-1 pada pakan ikan nila yang terpapar Pb (timbal) kon- sentrasi 9,119 mg L-1 dapat menurunkan nilai akumulasi logam Pb dan nilai malondialdehid hati ikan mencapai 1,47 mg kg-1 dan 5,41 µg g-1 .